Trend in disease burden of leukemia in China, 1990 - 2019 - Meng-na DAI; Yan XI; Wen-qiang YIN (Editorial Office of Chinese Journal of Public Health, 2022)
Objective To examine the disease burden of leukemia and its changing trend in China during 1990 - 2019 for providing a reference to strategy development of intervention and treatment of leukemia in China. Methods The data on leukemia incidence, mortality, and disability adjusted life year (DALY) in China were extracted from the database of the Global Burden of Disease Study 2019. Standardization was conducted for the incidence, mortality, and disability rate and Joinpoint regression model was adopted to analyze chronological trends in the standardized rates and to find meaningful turning points of the changing rates. Results The mortality, incidence rate and DALY of leukemia in China have been decreasing form 1990 to 2019. During the period for the standardized rates of leukemia, the mortality decreased averagely per year by 1.8% (1.5% for males and 2.2% for females), the incidence by 2.4 (2.1% for males and 2.2% for females), and the DALY by 1.8% (0.4% for males and 1.0% for females), respectively. The differences in the decreases of leukemia incidence, mortality and DALY rate were all statistically significant among general, male and female populations. Conclusion The disease burden of leukemia in China has decreased during 1990 - 2019, but the incidence rate has started to rebound. Under the influence of urbanization, industrialization and aging in China, the disease burden of leukemia may continue to increase, and it is necessary to strengthen researches on pathogenesis and risk factors of leukemia for developing effective intervention measures in high risk populations to slow down the increase in disease burden the disease.